Hirschsprung’s Disease Diagnosis: A Comparison of Calretinin and CD56 Immunohistochemistry - Dalya Sabah Najm Aldeen; Rafal Abdulrazaq Al-rawi; Kalthuma Salih Hamad Amen (Advanced Medical Journal)
Background & objectives: Hirschsprung’s disease is attributable to the congenital lack of ganglion cells in the far intestine. Rectal biopsy is deemed critical for its testing. In some instances, regular techniques fail to detect it. This study aims to evaluate the testing role of calretinin and CD56 immunohistochemistry and correlate the results to routine hematoxylin & eosin stained samples.